(untitled) (ModaPalavra e-periódico, 2013)
The article seeks to establish a relationship between History and Memory, by working museum that deals with photography as a document. In this context, the photograph - the attribute of a trace of what happened - supports the construction of an image that refers to the past, in the reminiscences of manners and fashions of yesteryear and now. Thus, photography, holds memories, presents itself as an object of study and analyze the social, historical, anthropological and political, that because the originator of the photo to the Museum is treated as the author of your own story.